Context‐relevant risk and protective factors for children in rural communities: Long‐term implications for adulthood educational and mental health outcomes. Issue 2 (15th June 2022) - Shen, Wensong; Hannum, Emily
Abstract: Globally, rural children are more likely than others to experience barriers to opportunity. We propose context‐relevant family risk and protective factors for children in rural villages in one of China's poorest provinces and analyze long‐term implications for educational and mental health outcomes in early adulthood. Four proposed risk factors—low parental education, insufficient income, parental migration, and parental ill‐health—show statistically significant detrimental implications for educational attainment. Low parental education stands out, with negative estimated effects on all outcomes. Insufficient income predicts higher scores for depression but not self‐esteem. Parental migration and parental ill health have no significant relationships with mental health outcomes. Proposed protective factors– parental warmth, doing things together, and household credit limit—have positive estimated effects on educational attainment, but not on most mental health outcomes. Few interactions between protective and risk factors exist, and patterns are generally similar for girls and boys.